OVERCOMING THE CONSEQUENCES OF WORK AT THE END OF 1932 OF THE SPECIAL L. M. KA-GANOVICH COMMISSION IN THE KUBAN (BY THE EXAMPLE OF AN ADVANCED COLLECTIVE FARM) - A. Skorik (Гуманитарные и юридические исследования)
Against the background of unceasing journalism generalizations about the perniciousness of Soviet collectivization of agriculture, the real consequences of one of the odious actions of the Stalinist agrarian policy related to the direction of the special L.M. Kaganovich commission in the North-Caucasus region. The novelty of the research undertaken by the author lies in the search for positive historical facts that destroy the negative trends in post-Soviet historiography in relation to collectivization. Hundreds of advanced (or strong, in the terminology of that time) collective farms, although they did not constitute the majority among the agricultural cartels of the North-Caucasus Territory, were able not only to withstand, but also to maintain production potential under the administrative pressure on the «breakdown of kulak sabotages Using the advanced (strong) Kuban collective farm «Khleborob-Lenin No.2» as an example, the article discusses the basic socio-economic indicators of 19321934 of a separate agricultural artel that survived a severe external impact. The relevance of the undertaken research consists in upholding the principle of scientific objectivity in relation to the facts of Soviet history politicized in historiography and journalism, which include collectivization of agriculture. Also, the significance of the work lies in a detailed micro historical analysis of the problem posed with the aim of identifying different vector processes and understanding the positive dynamics of the socio-economic indicators of the above-mentioned advanced (strong) Kuban collective farm as an illustrative example.